Knowledge in a group of pregnant women about dental caries in children - Morales-Canova, Claudia Alexandra (2024)
Objective: Determine the level of knowledge in pregnant women treated at the Inmaculada clinic in the district of Sullana about dental caries in children, during the months of July, August and September of 2023. Methodology: This study was quantitative, cross-sectional and prospective. The sample consisted of 145 pregnant women attended at the Inmaculada clinic in the district of Sullana, Piura. For data collection, a validated questionnaire was used, which was applied to the pregnant women when they attended the clinic. Descriptive statistics were applied for univariate analysis using frequency distribution and percentages. Results: The level of knowledge of pregnant women about dental caries in children in general was 60%, which corresponds to the regular level, 20.7%, which corresponds to the bad level, and 19.3%, which corresponds to the good level. It was identified that 72.4% of pregnant mothers have two or more children and of this percentage, 44.1% have a regular level of knowledge. The age group most frequently belongs to pregnant women between 31 and 40 years old, representing 52.4%, of which 32.4% have a regular level of knowledge. According to the level of education, the higher level represents 66.9% of pregnant mothers and of this amount, 39.3% have regular level knowledge; 75.2% of the pregnant mothers who participated in the study represent the urban sector, of which 46.2% have a regular level of knowledge about dental caries in children. Conclusion: The level of knowledge in pregnant women treated at the Inmaculada clinic in the district of Sullana about dental caries in children was generally at a regular level in all the variables studied.